1990
DOI: 10.1302/0301-620x.72b3.2341458
|View full text |Cite
|
Sign up to set email alerts
|

The treatment of ingrowing toenails. A randomised comparison of wedge excision and phenol cauterisation

Abstract: We treated 249 patients for ingrowing toenails in a prospective randomised study which compared wedge excision with segmental phenol cauterisation. Follow-up of 97% was at a minimum of 14 months. The analgesic requirement was significantly lower after phenol cauterisation (p less than 0.001), and significantly fewer patients needed to miss school or work (p = 0.001). Recurrence of ingrowth was seen in 16% after wedge excision and 9.6% after phenol cauterisation (not significant), but re-operation was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
0
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 0 publications
7
51
0
1
Order By: Relevance
“…For example, the Winograd technique, a type of wedge excision with removal of the lateral matrix horn and preservation of the lateral nail fold, was described as more painful than phenol cauterization. Also, it requires longer periods for sick leave and has a greater incidence of recurrence (6,11). A study of 100 patients with ingrown toenails treated with the conservative guttersplint method or Winograd technique reported that although the recurrence rate was lower for the patients treated with Winograd technique, the postoperative loss of work was much longer (2 weeks with the Winograd technique and 1.1 weeks with the gutter-splint method) (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the Winograd technique, a type of wedge excision with removal of the lateral matrix horn and preservation of the lateral nail fold, was described as more painful than phenol cauterization. Also, it requires longer periods for sick leave and has a greater incidence of recurrence (6,11). A study of 100 patients with ingrown toenails treated with the conservative guttersplint method or Winograd technique reported that although the recurrence rate was lower for the patients treated with Winograd technique, the postoperative loss of work was much longer (2 weeks with the Winograd technique and 1.1 weeks with the gutter-splint method) (19).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment method for the ingrown toenail primarily depends on the Heifetz classification stage, the degree of inflammation, and the preference of the physician, surgeon, or pedicurist (6)(7)(8)10). Most physicians prefer noninvasive, conservative treatments such as taping, packing with cotton or dental floss, gutter treatment, or nail braces or similar devices (2,8,11).…”
Section: Introductionmentioning
confidence: 99%
“…It mainly affects the great toes of men. 1-2 Approximately 20 percent of patients consulting family physicians with a foot problem have an ingrown toenail. 3 It leads to economic losses, affecting daily life, sporting and work activities.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] The combination of proximolateral partial matricectomy and phenol ablation achieves the lowest recurrence rate and provides the best cosmetic outcome. To the best of our knowledge, this is the fi rst study to assess this technique when performed using a modifi ed version of the Zadik method for matricectomy.…”
mentioning
confidence: 99%